Isolated Mesenteric Tuberculosis - Ghimire, Roshan; Laudari, Uttam; Singh, Deepak Raj (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Abdominal tuberculosis is common in developing world, and abdominal tuberculosis is most common presentation of extra pulmonary tuberculosis. High index of suspicion is needed in patient from endemic area with chronic abdominal pain and constitutional symptom for diagnosis of abdominal tuberculosis. In abdominal tuberculosis although intestinal, cecal and lymph node involvement are common, isolated mesenteric tuberculosis is rare presentation and very few cases has been reported. Here we are presenting rare case of a young male with isolated mesenteric tuberculosis who presented with abdominal mass.